Implementing English Augmented Reality Flashcards For Primary School Students: A Need Analysis - Prastiti, Khoirunnisa Candra; Rachmawati, Arandha May; Pratiwi, Nova Indriana; Yulia, Yuyun; Wahid, Muhammad Nurdin (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
Vocabulary is one of the foundations of the English language learning; mastering it is detrimental to language mastery. However, it was found that motivation, or lack thereof, is problematic. Needs analysis aims to identify what students and teachers need in learning English. The limited use of interactive learning media results in students being less motivated. Teachers who have limitations in using ICT are an obstacle to following current educational trends. AR flashcards have emerged to be offered as a learning medium.  The aim of this research is to analyze the needs of students and teachers in the English learning process, especially vocabulary learning. This research used a mixed method with the research subjects being fifth grade students and English teachers at SD N Pucung. Use of questionnaires in the form of close - ended questions and interviews as instruments in collecting the data. The research results showed that students and teachers needed more interactive learning media. Therefore, it is necessary for implementing AR Flashcards to increase student motivation in learning English vocabulary so that it becomes interesting and interactive.